(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Bovine trichomoniasis is a venereal disease caused by the protozoa Tritrichomonas foetus. The aim of the study was to investigate the prevalence of T. foetus in cattle and associated risk factors. A total of 200 samples from 183 cows and 17 bulls were collected from Veterinary Teaching Hospital, Bangladesh Agricultural University; Mymensingh district and Regional station of Bangladesh Livestock Research Institute in Shahjadpur, Sirajgonj during the period from March 2015 to May 2016. Among 200 cattle, 65 were indigenous, 100 were Holstein cross and 35 were Shahiwal cross bred. The collected samples were vaginal and uterine washing, aborted foetus and semen. The samples were collected from vagina and uterus by flashing with phosphate buffer solution by artificial insemination tube connected with 20 ml syringe. The samples were examined for T. foetus under microscope. The samples were examined on the same day of collection. Out of 200 samples examined, 3 (1.5%) were found infected with T. foetus protozoa. Among these 3 positive cases of tritrichomoniasis, one was detected in aborted foetal materials and other two were detected in vaginal washings. We did not find any T. foetus in the semen samples from the bulls. Therefore, bulls represent zero prevalence of T. foetus. During the study period the examined animals were categorized into three age groups viz. 40, 60 and 100 cattle for below 3 years, over 3 years to below 6 years and over 6 years to ten years, respectively. The prevalence rate was found in adult cattle over 6 years (>610 years) was 2.00%, over 3 years (>36 years) was 1.66% and below 3 years (<3 years) was 0%. In the study, prevalence rate of cross bred animals were 2.22% and no infection was found in indigenous bred. So, this preliminary study indicates that a low prevalence rate of bovine trichomoniasis present in cattle in this study area. Further investigation using serological and molecular method will help to detect precisely the prevalence of this important sexually transmitted protozoan disease in cattle. To our best knowledge, this is the first study on the prevalence of bovine tritrichomoniasis in Bangladesh except a single clinical case reported in 1974. This study also indicate that bovine tritrichomoniasis has a minor role related to abortion of cattle in Bangladesh. J. Bangladesh Agril. Univ. 15(1): 47-54, January 2017